If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(x + -4) = 2x + 5 Reorder the terms: 3 + -1(-4 + x) = 2x + 5 3 + (-4 * -1 + x * -1) = 2x + 5 3 + (4 + -1x) = 2x + 5 Combine like terms: 3 + 4 = 7 7 + -1x = 2x + 5 Reorder the terms: 7 + -1x = 5 + 2x Solving 7 + -1x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + -1x + -2x = 5 + 2x + -2x Combine like terms: -1x + -2x = -3x 7 + -3x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + -3x = 5 + 0 7 + -3x = 5 Add '-7' to each side of the equation. 7 + -7 + -3x = 5 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 5 + -7 -3x = 5 + -7 Combine like terms: 5 + -7 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 12s^3+22s^2-70s=0 | | [10-5(x-2)]=(x+1) | | 5+5w=2+11w | | 6x-3=15-48 | | 3/x=9/2 | | 7/8*h=1/5 | | 35u^2-39u-14=0 | | 10.1+5.3=w | | 1=y(8y-4) | | 1,34x-5,4=x-3,7 | | 2*2=5y | | X^2+18+20=0 | | 4x=y(4x-4) | | -(14-2s)-(6s+4)=14 | | 4x^3+14x^2+166x+140=0 | | 4xy-4y-4x=0 | | 5r^2-6r+1=0 | | (31-0.5y)+(31-0.5y+4)+y=66 | | y=70+14(7) | | 2*40+3x=128 | | 73=x+0.32x | | 6x+ay=24 | | 2x+9x-4x=14+7 | | 0.03/9 | | 3x+ay=15 | | -2t^2+15t-15=0 | | x*x-v*v= | | 5x^2+21x-24=0 | | 10=x+0.32x | | 2(3x+1)-8=30 | | 2x+y=62 | | 5x-2(x-4)=41 |